Phenotypic and genomic hallmarks of a novel, potentially pathogenic rapidly growing Mycobacterium species related to the Mycobacterium fortuitum complex - Reem Gharbi (Nature Portfolio, 2021)
Abstract Previously, we have identified a putative novel rapidly growing Mycobacterium species, referred to as TNTM28, recovered from the sputum of an apparently immunocompetent young man with an underlying pulmonary disease. Here we provide a thorough characterization of TNTM28 genome sequence, which consists of one chromosome of 5,526,191 bp with a 67.3% G + C content, and a total of 5193 predicted coding sequences. Phylogenomic analyses revealed a deep-rooting relationship to the Mycobacterium fortuitum complex, thus suggesting a new taxonomic entity. TNTM28 was predicted to be a human pathogen with a probability of 0.804, reflecting the identification of several virulence factors, including export systems (Sec, Tat, and ESX), a nearly complete set of Mce proteins, toxin-antitoxins systems, and an extended range of other genes involved in intramacrophage replication and persistence (hspX, ahpC, sodA, sodC, katG, mgtC, ClpR, virS, etc.), some of which had likely been acquired through horizontal gene transfer. Such an arsenal of potential virulence factors, along with an almost intact ESX-1 locus, might have significantly contributed to TNTM28 pathogenicity, as witnessed by its ability to replicate efficiently in macrophages. Overall, the identification of this new species as a potential human pathogen will help to broaden our understanding of mycobacterial pathogenesis.